Das Eismeer – Caspar David Friedrich and the North - Hinrichs, Nina (Nordlit, 2008)
The German Romantic painter Caspar David Friedrich (1774- 1840) created the work of art Das Eismeer in the years 1823/24. Besides his painting Mönch am Meer it is his most radical painting. It depicts a dramatic and grim subject: A shipwreck in the Arctic Sea. According to different cultural, historical and social contexts there have been many different interpretations of his painting since it was produced.